A new troglobitic species of the genus Leptomeson Jeannel, 1924 (Coleoptera: Leiodidae: Cholevinae: Leptodirini) from the Island of Šolta (middle Dalmatia, Croatia) - Ćurčić, Srećko; Vesović, Nikola; Lazović, Vladimir; Pantelić, Dejan; Rađa, Tonći (Zootaxa, 2019)
Leptomeson Jeannel, 1924, originally treated as a subgenus of Anthroherpon Reitter, 1889 (Jeannel, 1924), was erected to a distinct genus by Guéorguiev (1990). It currently includes 13 endemic taxa (nine species and four subspecies) (Perreau, 2015), of which five species are recently described (Giachino et al., 2011). All Leptomeson taxa are troglobitic, montane or insular, and are distributed in a narrow Dinaric area in the proximity to the Adriatic Sea coast belonging to Croatia and Bosnia and Herzegovina (Perreau, 2000; Giachino et al., 2011) (Fig. 1).